Respuesta :

Answer:

[tex]x=6\sqrt{3}[/tex]

Step-by-step explanation:

see the attached figure with letters to better understand the problem

step 1

In the right triangle ABC

Applying the Pythagoras Theorem

Find out the length side AB

[tex]AC^2=AB^2+BC^2[/tex]

[tex]AB^2=AC^2-BC^2[/tex]

substitute the given values

[tex]AB^2=12^2-x^2[/tex]

[tex]AB^2=144-x^2[/tex]

step 2

In the right triangle ABD

Applying the Pythagoras Theorem

Find out the length side BD

[tex]AB^2=AD^2+BD^2[/tex]

[tex]BD^2=AB^2-AD^2[/tex]

substitute the given values

[tex]BD^2=144-x^2-3^2[/tex]

[tex]BD^2=144-x^2-9[/tex]

[tex]BD^2=135-x^2[/tex] -----> equation A

step 3

In the right triangle BCD

Applying the Pythagoras Theorem

Find out the length side BD

[tex]BC^2=DC^2+BD^2[/tex]

[tex]BD^2=BC^2-DC^2[/tex]

substitute the given values

[tex]BD^2=x^2-9^2[/tex]

[tex]BD^2=x^2-81[/tex] -----> equation B

step 4

equate equation A and equation B

[tex]BD^2=135-x^2[/tex] -----> equation A

[tex]BD^2=x^2-81[/tex] -----> equation B

[tex]x^2-81=135-x^2[/tex]

[tex]x^2+x^2=135+81[/tex]

[tex]2x^2=216[/tex]

[tex]x^2=108[/tex]

[tex]x=\sqrt{108}[/tex]

Simplify

[tex]x=6\sqrt{3}\ units[/tex]

Ver imagen calculista